Antifungal Activity and Cytotoxicity to Human Gingival Fibroblast of Terminalia Bellirica Compounds in Dichloromethane Fraction - Pipatphatsakorn, Mayurach; Temkitthawon, Prapapan; Teenawong, Chanyanuch; Tanthasane, Ratjit; Wongwiriya, Anchapak; Damrongwanich, Orawee; Chailom, Karnhathai; Lohpongpanich, Nattaya; Thongpenyai, Parnfun; Detpong, Watis (Chiang Mai Dental Journal, 2018)
The aims of this study were to evaluate anticandidal effect of Terminalia bellirica compounds in dichloromethane fraction on Candida albicans and to determine the cytotoxic effect on human gingival fibroblasts. Dried Terminalia bellerica crude ethanolic extract was extracted by liquid-liquid extract technique. Fractionated ethanolic was separated into 5 fractions orderly by its polarity; hexane fraction, dichloromethane fraction, ethyl acetate fraction, butanol fraction and aqueous fraction. Antifungal activity against Candida albicans (ATCC 90028) of all fractioms was determined using disc diffusion method. In this study, the only dichloromethane fraction showed the effect against Candida albicans. Then, the lowest concentration of Terminalia bellirica compounds in dichloromethane fraction that exhibited anticandidal activity on disc diffusion assay was used as initial concentration in microbroth dilution. The results showed the minimum concentrations of Terminalia bellerica compounds in dichloromethane fraction that inhibited 96.51% and 99.93% of Candida albicans growth were 20 mg/ml and 25 mg/ml, respectively. Gingival tissue samples were collected from 3 subjects. The gingival tissues were harvested during a surgical procedure of impacted tooth removal. Human gingival fibroblast cultures were obtained from gingival explants. The fibroblasts were cultured in cell culture medium without serum and treated with various concentrations of Terminalia bellirica compounds in dichloromethane fraction for 24 hours. Dichloromethane fraction-free wells were used as a control condition. Cells viability was determined by using the MTT solution and the optical density (OD) was measured using microplate reader (wave length 570 nm). The Terminalia bellirica compounds in dichloromethane fraction at concentration of 625 µg/mL was the maximum concentration that had no cytotoxicity on human gingival fibroblasts (p≥0.01) whereas the maximum fungicidal concentration of Terminalia bellirica compounds in dichloromethane fraction was 25,000 µg/ml. Thus, the dichloromethane fraction of Terminalia bellirica compounds need more studies for further be used clinically in oral medicine.